The application of biochar mitigated the negative effects of freeze-thaw on soil and nutrient loss in the restored soil of the alpine mining area - Li, Fayong; Wang, Desheng; You, Yongjun; Li, Guoyu; Eltohamy, Kamel Mohamed; Khan, Sangar; Riaz, Luqman (Frontiers in Environmental Science, 2022)
Mining operations accelerate ecological damage in alpine mountain locations by contributing to soil erosion and nutrient loss in the freeze-thaw (FT) climate. However, limited studies have been conducted to reduce the soil erosion and nutrient loss in FT climate. This study's goal was to determine how biochar effected soil erosion in the restored soil of the alpine mining region under FT circumstances. Rainfall simulation and FT cycles (FTCs; 3 and 5) were used to investigate the effects of 500 and 1000 kg hm−2 biochar application rates (BARs) on runoff, soil loss, and runoff loss of ammonia nitrogen (AN), nitrate nitrogen (NN), total phosphorus (TP), and dissolved phosphorus (DP). Soil residual AN, NN, and DP concentrations after FTCs were also evaluated. Biochar application significantly reduced the runoff, soil loss rate, AN and NN loss rates, but increased the runoff NN concentration and decreased the total AN and NN loss under FTCs condition. Reductions in AN (37.2%–52.2%) and NN (14.3%–27.1%) runoff loss can be differentially attributed to the adsorption effect of biochar and decrease in total runoff. The runoff P concentrations, rates, and magnitudes for soils subjected to FTCs significantly decreased with biochar addition, owing to the particulate P loss decrease in soil and increased adsorption effect of soil DP. Biochar addition increased soil residual AN, NN, and DP concentrations. However, the increase in FTCs weakened the inhibitory effects of biochar on soil erosion. This study suggested the important role of biochar application for the recovery of low-nutrient eroded soils in alpine mining areas.